(untitled) (Research, Society and Development, 2021)
This study set one´s sight on the relationship between lower quarter y balance test (YBT-LQ) score with hip isometric strength with recreationally resistance-trained women. Utilizing dynamic balance as a screening tool for lower extremity injury risk has been proposed as a potential solution in injury prevention and injury assessment. A convenience sample of twenty young college females (22.3 ± 2.1 years) with a background in regular strength or plyometric training volunteered to participate in this study. The scores of YBT-LQ for each direction were calculated. A hand-held dynamometer was used to measure the maximum voluntary isometric strength of each participant´s unilateral hip extensors, flexors, adductors, abductors, internal and external rotation muscles. Significant lower normalized score was noted for the dominant limb (81.2 ± 11.7) when compared to non-dominant limb (83.6 ± 12.4) for anterior distance. For the composite score of YBT-LQ, a weak association was noted for hip extension and internal rotation, and moderate association was observed for hip flexion, adduction, and abduction. On the other hand, a strong association was observed between hip external rotators strength (r =0.516). Thus, the main finding of the current study was the strong association observed between hip external rotators strength and composite score of YBT-LQ.